Pelindungan Data Pribadi pada Layanan Pendanaan Berbasis Teknologi Informasi Pasca Undang-Undang Nomor 27 Tahun 2022 dan Undang-Undang Nomor 4 Tahun 2023 - Theresa, Gita; Marlyna, Henny (UI Scholars Hub, 2024)
Abstract Information Technology-Based Crowdfunding Services (LPBBTI) continue to encounter challenges related to legal protections, such as breaches of privacy and the misuse of personal data belonging to consumers and the public. This paper analyzes the implementation of personal data protection through LPBBTI operational compliance, the drafting of privacy policies and LPBBTI agreements, as well as the role of authorities in overseeing LPBBTI operators in implementing personal data protection following the enactment of Law No. 27 of 2022 (UU PDP) and Law No. 4 of 2023 (UU P2SK). This study aims to provide information and input on the implementation of consumer personal data protection laws in the financial sector, particularly in the operation of LPBBTI. The study found that personal data protection is implemented through compliance with business processes, the formulation of privacy policies ensuring consumer consent, and LPBBTI agreements that include clauses on the use of personal data, in accordance with UU PDP, and UU P2SK and its derivative regulations. Additionally, through market conduct supervision, the Financial Services Authority (OJK) is authorized to oversee compliance with personal data protection regulations and impose administrative sanctions in accordance with regulations in the financial sector. Keywords: Consumers, Personal Data Protection, LPBBTI